Dietary L-Carnitine Affects Leukocyte Count and Function in Dairy Cows Around Parturition - Kononov, Susanne Ursula; Meyer, Jennifer; Frahm, Jana; Kersten, Susanne; Kluess, Jeannette; Bühler, Susanne; Wegerich, Anja; Rehage, Jürgen; Meyer, Ulrich; Huber, Korinna; Dänicke, Sven (Frontiers in Immunology, 2022)
In early lactation, an energy deficit leading to a negative energy balance (NEB) is associated with increased susceptibility to disease and has been shown to be an important factor during transition in dairy cows. L-carnitine as a key factor in the mitochondrial transport of fatty acids and subsequently for β-oxidation and energy release is known to modulate mitochondrial biogenesis and thus influence metabolism and immune system. In the current study, we characterized hematological changes around parturition and investigated the potential effects of dietary L-carnitine supplementation on immune cell functions. For this approach, dairy cows were assigned either to a control (CON, n = 30) or an L-carnitine group (CAR, n = 29, 25 g rumen-protected L-carnitine per cow and day (d)). Blood samples were taken from d 42 ante partum (ap) until d 110 post-partum (pp), with special focus and frequent sampling from 0.5 to72 h post-calving to clarify the impact of L-carnitine supplementation on leukocyte count, formation of reactive oxygen species (ROS) in polymorphonuclear cells (PMN) and peripheral mononuclear cells (PBMC) and their phagocytosis activity. Blood cortisol concentration and the capacity of PBMC proliferation was also investigated. All populations of leukocytes were changed during the peripartal period, especially granulocytes showed a characteristic increase up to 4 h pp. L-carnitine supplementation resulted in increased levels of eosinophils which was particularly pronounced one day before to 4 h pp, indicating a possible enhanced support for tissue repair and recovery. Non-supplemented cows tended to have elevated non-esterified fatty acids levels, which may be related to higher phagocytic activity in PBMC as well as a higher phagocytic capacity of PMN during the most demanding period around parturition. L-carnitine, on the other hand, led to an increased efficiency to form ROS in stimulated PMN. Finally, a short period around calving proved to be a sensitive period in which L-carnitine administration was effective.